2019
DOI: 10.31557/apjcp.2019.20.8.2365
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neutrophil–Lymphocyte Ratio as a Prognostic Factor in Cervical Intraepithelial Neoplasia Recurrence

Abstract: Background: Immune system status is a factor related to cervical intraepithelial neoplasia (CIN) recurrence. neutrophil-lymphocyte ratio (NLR) is a useful factor in assessing the immune status. The aim of this study was to evaluate the prognostic value of NLR factor for CIN recurrence in patient who underwent excisional procedure and its relationship with recurrence free survival (RFS). Methods: In this historical cohort study, a population of 307 patients with CIN (confirmed by excisional pathology) from 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 24 publications
0
27
1
1
Order By: Relevance
“…The most important difference of our study from the ones in the literature is that patients who have just been met to the virus and have not yet developed malignancy were included in our study, while the patients who have already developed malignancy had been analysed in other studies in the literature. The reason for the difference in the results of some studies in the literature may be that patients with malignancies of different stages and sizes were included in those studies (Huang et al., 2015; Chun et al., 2017; De Felice et al., 2019; Li et al., ,2016, 2017; Wu et al., 2017; Farzaneh et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The most important difference of our study from the ones in the literature is that patients who have just been met to the virus and have not yet developed malignancy were included in our study, while the patients who have already developed malignancy had been analysed in other studies in the literature. The reason for the difference in the results of some studies in the literature may be that patients with malignancies of different stages and sizes were included in those studies (Huang et al., 2015; Chun et al., 2017; De Felice et al., 2019; Li et al., ,2016, 2017; Wu et al., 2017; Farzaneh et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on different types of solid tumors (cervical cancer), such as genetic instability at gene locus 1p36, which may be a feature of cervical cancer 22 ; decreased expression of cytokeratin 7 may lead to poor prognosis of cervical cancer 23 ; HPV infection is an important potential biomarker of cervical cancer 24 ; neutrophil ratio and white matter cell count can be used as a prognostic factor for recurrence of cervical cancer 25 . However, the continuous process from inflammation to CIN to invasive cancer is often overlooked.…”
Section: Resultsmentioning
confidence: 99%
“…It is also reported that ( Wisdom et al, 2019 ) neutrophils can increase the resistance of tumor cells to radiation therapy, and neutrophil-lymphocyte ratio can be considered as a predictor in stage IVB or recurrent cervical cancer patients treated by chemotherapy. Neutrophil-lymphocyte ratio ≥ 3.6 has been identified as an independent predictor of poor oncologic outcomes with respect to OS ( Farzaneh et al, 2019 ; Ittiamornlert and Ruengkhachorn, 2019 ). These data suggest that the relationship between the risk score provided by the IRG signature model and neutrophil infiltration is well-established.…”
Section: Discussionmentioning
confidence: 99%